2013
DOI: 10.1093/bib/bbt050
|View full text |Cite
|
Sign up to set email alerts
|

A model for family-based case-control studies of genetic imprinting and epistasis

Abstract: Genetic imprinting, or called the parent-of-origin effect, has been recognized to play an important role in the formation and pathogenesis of human diseases. Although the epigenetic mechanisms that establish genetic imprinting have been a focus of many genetic studies, our knowledge about the number of imprinting genes and their chromosomal locations and interactions with other genes is still scarce, limiting precise inference of the genetic architecture of complex diseases. In this article, we present a stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…To test this hypothesis we used our recently developed model[27] that has been demonstrated to be genetically meaningful in our previous studies on IBD susceptibility genes[30,35,36]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test this hypothesis we used our recently developed model[27] that has been demonstrated to be genetically meaningful in our previous studies on IBD susceptibility genes[30,35,36]. …”
Section: Resultsmentioning
confidence: 99%
“…Using this model we have previously studied epistatic interaction between SNPs within the DLG5 gene and between IBD genes DLG5 , OCTN1 , IL23R and NOD2 [28,35,36], and found that epistatic interaction is an important component in IBD pathogenesis. In this study, we used the same method to study gene-gene interaction in IL-10 signaling transduction pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Basically, these designs include outcrossed families [29,74], sex-specific linkage analysis [19,25], reciprocal crosses [90,148,149,192], multigenerational pedigrees [92], open-pollinated populations [138] and case-control studies [87]. From these designs, significant imprinted QTLs were detected for body composition and body weight in pigs, chickens, sheep and canine, endosperm traits in maize, and stem growth in hickory tree.…”
Section: Modeling the Genetic Architecture Of Complex Traitsmentioning
confidence: 99%
“…Hanson et al [19] extended a variance-components approach to test for parent-of-origin effects by sampling siblings. Li et al [20] proposed a multi-locus likelihood method for investigating parent-of-origin effects on the basis of case-control mother-child pairs. However, these methods are proposed for detecting the effects on autosomal alleles instead of alleles on the X chromosome.…”
Section: Introductionmentioning
confidence: 99%